MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MENULIS CERITA FABEL DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS VIII-C SMP NEGERI 5 TENGGARONG - NFN Jumairi (Kantor Bahasa Kalimantan Timur, 2017)
This study aimed to increase the activity and the learning outcome of writing fabel using Student Team Achievement Division (STAD) cooperative learning model in grade VIII-C of Smp Negeri 5 Tenggarong. It was conducted in three cycles and each cycle consisted of four stages, namely planning, action, observation, and reflection. The result showed that the use of STAD cooperative learning model in the learning of writing fable could improve grade VIII-C SMP Negeri 5 Tenggarong students’ activity and learning outcomes in academic year 2016/2017.